2012
DOI: 10.1016/j.jaci.2012.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Protection from asthma in a high-risk birth cohort by attenuated P2X7 function

Abstract: Background Viral illnesses are important factors in both asthma inception and exacerbations, and allergic sensitization in early life further enhances asthma risk through unclear mechanisms. Cellular damage due to infection or allergen inhalation increases ATP in the airways with subsequent purinergic receptor activation. The purinergic receptor P2X7 may enhance airway leukocyte recruitment to the airways and P2X7 knockout mice display a reduced asthma-like phenotype. Objective Based upon the P2X7 knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…71,73 In addition, low-functioning P2X 7 receptor variants have been shown to be associated with reduced risks of childhood asthma and allergic sensitization in a birth cohort at high risk for the development of asthma. 76 Overall, these results suggest that the P2Y 2 , P2Y 6 , and P2X 7 receptor subtypes could represent new therapeutic targets to treat allergic lung inflammation.…”
Section: P2y 6 Receptormentioning
confidence: 86%
“…71,73 In addition, low-functioning P2X 7 receptor variants have been shown to be associated with reduced risks of childhood asthma and allergic sensitization in a birth cohort at high risk for the development of asthma. 76 Overall, these results suggest that the P2Y 2 , P2Y 6 , and P2X 7 receptor subtypes could represent new therapeutic targets to treat allergic lung inflammation.…”
Section: P2y 6 Receptormentioning
confidence: 86%
“…Although more in vivo studies are welcome to confirm the observations made on the models of asthmatic inflammation, targeting P2 receptor function might indeed represent a promising approach to develop new therapeutics for asthma as evidenced by a recent study in a birth cohort at high risk for development of asthma that reported an attenuated P2X7 function to be associated with lower asthma rates [143] (Table 1).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…In addition, blood neutrophils harvested from the patients with COPD show a stronger chemotaxis and an elastase release in response to ATP treatment compared with the control subjects (92). In patients with asthma, in addition to increased levels of ATP in BALF, the functional activity or Single Nucleotide Polymorphism of P2X7R is also associated with the exacerbation or severity of asthma (33,96). While the pathogenesis of these lung diseases differs from each other, inflammatory responses are commonly involved in the development and acute exacerbation of these diseases.…”
Section: Plasmamentioning
confidence: 99%